Космос: справочник школьника / С. Ю. Модестов - Модестов Сергей Юрьевич (Логосвос, 2006)
Экземпляры: БС (20170912) / Инвентарный номер: РТШ50598 / Сис.шифр: 22.6 / Авт.знак: М 74 / ГРНТИ: 41.29 / ББК: 22.6я2